Atuação do farmacêutico na faringoamigdalite estreptocócica e sua relação com a prevenção da febre reumática - Boff, Bianca Miotto (My University, 2025)
OBJECTIVE: To conduct an analysis of the pharmacist's role in Primary Health Care and to develop a complementary review on streptococcal pharyngotonsillitis and its contribution to the prevention of rheumatic fever, highlighting its relationship within the context of the Unified Health System (SUS). METHODS: A narrative literature review was conducted using searches in the SciELO, PubMed, LILACS, CAPES Journals, and Google Scholar databases, as well as guidelines from scientific societies. Descriptors related to Streptococcus pyogenes, primary health care, pharmacist, rheumatic fever, and pharmaceutical assistance were used. Publications from 2015 to 2025, in Portuguese, English, and Spanish, were included. Materials relevant to the topic were selected, and sources with low reliability or incomplete data were excluded. The study used exclusively secondary data. RESULTS AND DISCUSSION: The results demonstrate that the effective participation of the pharmacist, integrated into the multidisciplinary teams of the SUS (Brazilian Public Health System), favors timely diagnosis, improves adherence to treatment, reduces complications, and strengthens health promotion and prevention actions. CONCLUSION: The review shows that the pharmacist has a strategic role in the SUS for the proper management of streptococcal pharyngotonsillitis and for the prevention of rheumatic fever. Their presence in Primary Health Care contributes to the rational use of medications, improves adherence to antibiotic treatment, expands educational actions, and strengthens multidisciplinary work. Strengthening pharmaceutical care and the clinical role of the pharmacist in Basic Health Units is fundamental to reducing the burden of rheumatic fever, especially in vulnerable regions. It is recommended to expand the training and inclusion of this professional in actions aimed at prevention and continuous health care. [resumo fornecido pelo autor]
OBJETIVO: Realizar uma análise sobre a atuação do farmacêutico na Atenção Primária à Saúde e desenvolver uma revisão complementar acerca da faringoamigdalite estreptocócica e sua contribuição para a prevenção da febre reumática, destacando sua relação no no contexto do Sistema Único de Saúde (SUS). MÉTODOS: Realizou-se uma revisão narrativa da literatura por meio de buscas nas bases SciELO, PubMed, LILACS, CAPES Periódicos e Google Acadêmico, além de diretrizes de sociedades científicas. Foram utilizados descritores relacionados a Streptococcus pyogenes, atenção primária à saúde, farmacêutico, febre reumática e assistência farmacêutica. Incluíram-se publicações de 2015 a 2025, nos idiomas português, inglês e espanhol. Foram selecionados materiais relevantes ao tema e excluídas fontes com baixa confiabilidade ou dados incompletos. O estudo utilizou exclusivamente dados secundários. RESULTADOS E DISCUSSÃO: Os resultados demonstram que a participação efetiva do farmacêutico, integrada às equipes multiprofissionais do SUS, favorece o diagnóstico oportuno, melhora a adesão ao tratamento, reduz complicações e fortalece ações de promoção e prevenção em saúde. CONCLUSÃO: A revisão evidencia que o farmacêutico tem papel estratégico no SUS para o manejo adequado da faringoamigdalite estreptocócica e para a prevenção da febre reumática. Sua presença na Atenção Primária à Saúde contribui para o uso racional de medicamentos, melhora a adesão ao tratamento antibiótico, amplia as ações educativas e fortalece o trabalho multiprofissional. O fortalecimento da assistência farmacêutica e da atuação clínica do farmacêutico nas Unidades Básicas de Saúde é fundamental para reduzir a gravidade da febre reumática, especialmente em regiões vulneráveis. Recomenda-se ampliar a capacitação e inserção desse profissional em ações voltadas à prevenção e ao cuidado contínuo em saúde. [resumo fornecido pelo autor]
Keywords: Farmacêuticos; Cuidados primários de saúde; Febre reumática; Assistência farmacêutica; Streptococcus pyogenes